Labour Diplomacy and Migration Governance in Nepal - Bashyal, Keshav; Subedi, Binita (Journal of Foreign Affairs, 2021)
This paper examines the linkage between labour diplomacy and migration governance, which is one of the most interconnected subjects in international relations. Especially in the case of Nepal, almost a quarter of the total working age population is working abroad and the remittance contributes to more than a quarter of its national GDP and greatly influences the socio-economic dynamics of Nepali society. Myriads of socio-economic tangibles, besides macroeconomic variables are intertwined with the country’s labour migration phenomena. The paper focusses on analysing different facets of this linkage by distinctly dissecting various issues concerning labour migration, including the gender perspective, on the diplomatic as well as governance front to explore the gap between the economic aspirations of the country and the actual pace of economic development. The paper uses qualitative methods to allow analytical assessment of various government as well as secondary sources of literature, including reports prepared by international bodies. This leads to the conclusion that without proper interlinkage and cooperation between labour diplomacy and migration governance, it is not possible to achieve sustainable economic growth and development of Nepal.